1991
DOI: 10.1177/019251391012001007
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Division of Household Labor

Abstract: Despite a large body of research on the household division of labor, surprisingly little is known about how husbands and wives divide their family work time across a variety of domestic tasks. What differentiates couples exhibiting gender specialization or segregation in household tasks from those couples who share tasks? Using newly released data from the National Survey of Families and Households, this study has two major objectives. First, a new summary measure of the gender-based segregation of family labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
20

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(106 citation statements)
references
References 24 publications
5
81
0
20
Order By: Relevance
“…On the one hand, because having children may be fulfilling a central life goal for many women, parenthood may be associated with greater life satisfaction, happiness with life in general, and self-esteem, especially when the responsibilities of child rearing are not overwhelming. On the other hand, although women have evidenced greater participation in the workforce (Bianchi, Milkie, Sayer, & Robinson, 2000;Blair & Lichter, 1991;England, 2010), mothers are paid less than childless women (Budig & England, 2001), and they still bear the brunt of child rearing (Milkie, Bianchi, Mattingly, & Robinson, 2002;Nock & Kingston, 1988;Nomaguchi & Milkie, 2003), which may engender lower day-to-day well-being. Consistent with this idea, research has shown that specifically among women, firstborn children are associated with relatively greater happiness (compared to women without children), but subsequent children are associated with relatively less happiness (Aassve et al, 2012;Kohler et al, 2005).…”
mentioning
confidence: 99%
“…On the one hand, because having children may be fulfilling a central life goal for many women, parenthood may be associated with greater life satisfaction, happiness with life in general, and self-esteem, especially when the responsibilities of child rearing are not overwhelming. On the other hand, although women have evidenced greater participation in the workforce (Bianchi, Milkie, Sayer, & Robinson, 2000;Blair & Lichter, 1991;England, 2010), mothers are paid less than childless women (Budig & England, 2001), and they still bear the brunt of child rearing (Milkie, Bianchi, Mattingly, & Robinson, 2002;Nock & Kingston, 1988;Nomaguchi & Milkie, 2003), which may engender lower day-to-day well-being. Consistent with this idea, research has shown that specifically among women, firstborn children are associated with relatively greater happiness (compared to women without children), but subsequent children are associated with relatively less happiness (Aassve et al, 2012;Kohler et al, 2005).…”
mentioning
confidence: 99%
“…The "feminine" tasks normally take more time and must be carried out more frequently, with less scheduling freedom. The "masculine" tasks are more fl exible and less frequent, require less time and in some cases can be considered related to leisure (Blair and Lichter, 1991).…”
Section: The Division Of Domestic Workmentioning
confidence: 99%
“…Даже в ситуа-ции значительной вовлеченности мужчины в семейные дела его участие обычно сводится к определенным видам деятельности [Blair, Lichter, 1991]. Уход за детьми также рассматривается как гендерно не нейтральный тип деятельности.…”
Section: о н борисова гендер и семьяunclassified
“…В противоположность гендерным теориям, утверждаю-щим, что такое распределение оказывает негативное влияние на вовлеченность мужчины, в данном случае более применимым оказывается ресурсный подход. Иными словами, можно утверждать, что речь идет о взаимодополняющем харак-тере распределения ролей между семьей и работой в зависимости от имеющихся у супругов ресурсов [Becker, 2009;Blair, Lichter, 1991].…”
Section: индивидуальные детерминантыunclassified